Transediting the terms used for describing the US dollar in Arabic and English news websites: a triangulational study of transediting strategies adopted in four channels - Alwazna, Rafat Y.; Al Hamed, Alawia A. (Frontiers in Communication, 2024)
News translation, which is often known as news transediting, which is concerned with the translation of materials for print and/or online mass media, has long stimulated interest within the field of translation studies. The present paper explores the strategies of transediting the terms used for describing the US dollar in the websites of four news channels, namely: Alarabiya, Aljazeera, BBC and CNN between Arabic and English from the first of July 2022 to the thirty-first of December 2022. The paper conducts triangulational analysis to identify the type and frequency of the transediting strategies used in each channel, present how certain examples of each strategy are adopted and demonstrate the similarities and differences in the type and frequency of the transediting strategies employed between the channels. The paper argues that the choice of the transediting strategy is based on the type of audience, context, the channel’s policy and the type of information intended for delivery. This paper offers a baseline for exploring the strategies of transediting the terms used for describing the US dollar in both Arabic and English news websites of the aforementioned channels, which may have implications for exploring other transediting strategies used in other news websites of different channels broadcast in different languages.